Disciplinary changes in science education in Hungary in the era of the Stalinist dictatorship - Imre Garai; András Németh (Charles University, 2018)
Abstract: In our paper we intend to summarize the main results of our research about the structural and disciplinary changes in Hungarian higher education in the early part of the 1950s. In the first part of our paper we point out the basic elements of the theoretical background to the research. Stichweh's notion of disciplines, Bourdieu's theory of 'scientific fields', and Voegelin's concept of 'political religion' made it possible to describe and analyze the complex phenomena involved in the socialist transformation of Hungarian higher education. Then, in the second part of the paper, we analyze the main data gained from archival research into the structural changes in higher education institutions by using the theoretical notions mentioned above. As a result of our research, we are able to determine some peculiarities of the socialist higher education policy and socialist educational discipline. Keywords: socialist notion of discipline, scientific field, Sovietization of higher education, Soviet influence in Central-Eastern Europe